Does media sentiment affect stock prices? Evidence from China’s STAR market - Dong, Xiuliang; Xu, Shiying; Liu, Jianing; Tsai, Fu-Sheng (Frontiers in Psychology, 2022)
This paper explores the impact of media sentiment on stock prices on the Shanghai Stock Exchange Science and Technology Innovation Board (hereinafter the STAR market) from a behavioral finance perspective. We collect Baidu News coverage of STAR-listed firms as the text, and measure text sentiment using a machine learning-based text analysis technique. We then empirically examine the impact of media sentiment on STAR market stock prices from two aspects: IPO pricing efficiency and IPO first-day stock performance. The results indicate the following findings. (1) Media sentiment has no significant impact on IPO pricing efficiency, thus suggesting that institutional investors participating in such offerings are generally not affected by media sentiment. (2) Optimistic media sentiment has a positive impact on IPO first-day returns, which indicates that individual investors are more easily influenced by media sentiment and therefore likely to abandon their rational judgment. (3) Media sentiment had a greater impact on IPO first-day returns during the COVID-19 pandemic than those before it, which suggests that individual investors are more influenced by media sentiment during pandemics. The results still hold after a series of robustness tests in which we change the sample period and employ alternative measurements of the variables. The findings of this study contribute to the literature by deepening our understanding of stock price formation on the STAR market and also providing a statistical basis for formulating policy directions and investment strategies.